Data from: Altitude effects on spatial components of vascular plant diversity in a subarctic mountain tundra - Naud, Lucy; Måsviken, Johannes; Freire, Susana; Angerbjörn, Anders; Dalén, Love; Dalerum, Fredrik (2019)
Environmental gradients are caused by gradual changes in abiotic factors, which affect species abundances and distributions, and are important for the spatial distribution of biodiversity. One prominent environmental gradient is the altitude gradient. Understanding ecological processes associated with altitude gradients may help us to understand the possible effects climate change could have on species communities. We quantified vegetation cover, species richness, species evenness, beta diversity, and spatial patterns of community structure of vascular plants along altitude gradients in a subarctic mountain tundra in northern Sweden. Vascular plant cover and plant species richness showed unimodal relationships with altitude. However, species evenness did not change with altitude, suggesting that no individual species became dominant when species richness declined. Beta diversity also showed a unimodal relationship with altitude, but only for an intermediate spatial scale of 1 km. A lack of relationships with altitude for either patch or landscape scales suggests that any altitude effects on plant spatial heterogeneity occurred on scales larger than individual patches but were not effective across the whole landscape. We observed both nested and modular patterns of community structures, but only the modular patterns corresponded with altitude. Our observations point to biotic regulations of plant communities at high altitudes, but we found both scale dependencies and inconsistent magnitude of the effects of altitude on different diversity components. We urge for further studies evaluating how different factors influence plant communities in high altitude and high latitude environments, as well as studies identifying scale and context dependencies in any such influences.